ESR1 testing on FFPE samples from metastatic lesions in HR + /HER2- breast cancer after progression on CDK4/6 inhibitor therapy - Konstantinos Venetis; Giulia Cursano; Roberta Scafetta; Pier Paolo Maria Berton Giachetti; Alberto Concardi; Elisa De Camilli; Marianna D’Ercole; Eltjona Mane; Chiara Frascarelli; Antonio Marra; Sara Gandini; Francesco Pepe; et al. (Breast Cancer Research)
Abstract Mutations in ESR1 play a critical role in resistance to endocrine therapy (ET) in hormone receptor-positive (HR +)/HER2- metastatic breast cancer (MBC). Testing for ESR1 mutations is essential for guiding treatment with novel oral selective estrogen receptor degraders (SERDs) like elacestrant or camizestrant. While most studies have utilized liquid biopsy (LB) for mutation detection, the role of formalin-fixed paraffin-embedded (FFPE) tissue biopsy in this context remains unclear. In this study, we analyzed a cohort of HR + /HER2- MBC patients who experienced resistance to ET and CDK4/6 inhibitors. Next-generation sequencing (NGS) was performed on FFPE biopsy samples obtained from metastatic sites at the time of disease progression. ESR1 mutations were detected in 24 out of 38 patients (63.2%), with p.D538G identified in 10 patients (45.5%) and p.Y537S in 6 patients (27.2%) as the most frequent alterations. One patient exhibited dual ESR1 mutations, and a recurrent ESR1-CCDC170 gene fusion was identified, underscoring the diversity and potential interplay of genetic alterations driving resistance in HR + /HER2- MBC. Notably, lung metastases were significantly more common in ESR1 mutant cases (8/24, 33.3%) compared to wild-type cases (1/14, 7.1%), while liver metastases showed no difference between mutant (12/24, 50.0%) and wild-type groups (7/14, 50.0%). Co-mutations in actionable pathways, particularly PIK3CA, were observed in n = 10 ESR1 mutant tumors (41.6%), highlighting their contribution to resistance mechanisms and posing significant challenges for treatment selection, as these alterations may necessitate combination therapies to effectively target multiple resistance pathways. This study presents new insights into the prevalence and clinical significance of ESR1 mutations in HR + /HER2- MBC, highlighting the potential utility of FFPE biopsy samples as a viable alternative or complementary approach to LB for mutation detection, particularly in resource-limited settings where access to ctDNA analysis may be constrained.